2019
DOI: 10.1353/hpu.2019.0011
|View full text |Cite
|
Sign up to set email alerts
|

Racial/Ethnic Disparities in Health Insurance and Differences in Visit Type for a Population of Patients with Diabetes after Medicaid Expansion

Abstract: This quasi-experimental study evaluated racial/ethnic disparities in health insurance and differences in visits post- versus pre- Affordable Care Act (ACA) Medicaid expansion. We utilized electronic health record data from a population of patients with diabetes aged 19–64 seen in community health centers (CHCs). We used generalized estimating equation Poisson models to estimate incidence rates of insurance type and visits post- (1/1/2014– 12/31/2015) versus pre- (1/1/13–12/31/13) ACA, stratified by racial/ethn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 19 publications
3
21
0
Order By: Relevance
“…In nonexpansion states, by contrast, we saw only a small decline in uninsured rates along with a slight increase in privately insured cancer survivors, which was not statistically significant. These findings follow previous studies of the overall CHC population 9,35 and patients with diabetes, 39,40 which showed reductions in uninsured rates and Figure 1. Adjusted likelihood of being uninsured, insured/uninsured, insured with Medicaid, or insured with some private insurance during each 2-year period (2012-2013, 2014-2015, and 2016-2017) by expansion status.…”
Section: Discussionsupporting
confidence: 90%
“…In nonexpansion states, by contrast, we saw only a small decline in uninsured rates along with a slight increase in privately insured cancer survivors, which was not statistically significant. These findings follow previous studies of the overall CHC population 9,35 and patients with diabetes, 39,40 which showed reductions in uninsured rates and Figure 1. Adjusted likelihood of being uninsured, insured/uninsured, insured with Medicaid, or insured with some private insurance during each 2-year period (2012-2013, 2014-2015, and 2016-2017) by expansion status.…”
Section: Discussionsupporting
confidence: 90%
“…Angier et al show that by race/ethnicity, White patients who enrolled in Medicaid within expansion states were older and had more comorbidities compared with both Hispanic and Black patients. [ 33 ] Our model adjusted for age, the number of chronic comorbidities, and the Elixhauser mortality score. Therefore, differential rates of comorbidity between newly enrolled White and non-White Medicaid patients, particularly Hispanic patients, may explain this LOS discrepancy as an artifact of risk-adjustment.…”
Section: Discussionmentioning
confidence: 99%
“…adherence to routine preventative eye care). The Hispanic population is more than twice as likely to be uninsured than the non-Hispanic white population, placing a great strain on access to needed early interventions [18]. Compared to non-Hispanic whites, Hispanics had lower levels of glycated hemoglobin (HbA1c) testing, eye exams, and other preventative health screenings [19].…”
Section: Discussionmentioning
confidence: 99%